Analisis Pemasaran Syariah dalam Meningkatkan Nasabah Produk BSI OTO Pada Bank Syariah Indonesia KCP Pinrang - Nasriani; Wahyuni; Rasyidah Bulqis (STAI DDI Pinrang, 2025)
BSI OTO is a motor vehicle financing service product (cars and motorbikes). This research aims to analyze Sharia Marketing in increasing customers for BSI OTO products. The method used is qualitative with interview techniques, observation and documentation. The research subjects were sharia bank employees and customers of BSI OTO KCP ​​Pinrang. The results of the study indicate that: 1) The BSI OTO Product System at Bank Syariah Indonesia KCP Pinrang uses the murabahah contract, which is a buying and selling scheme where the bank buys vehicles from dealers and resells them to customers at an agreed price, including a profit margin. 2) The sharia marketing strategy implemented by Bank Syariah KCP Pinrang in increasing the number of BSI OTO product customers is quite effective. This strategy includes promotion, distribution of brochures, socialization, and utilization of social media.